2007
DOI: 10.1126/science.1133376
|View full text |Cite
|
Sign up to set email alerts
|

Early Upper Paleolithic in Eastern Europe and Implications for the Dispersal of Modern Humans

Abstract: Radiocarbon and optically stimulated luminescence dating and magnetic stratigraphy indicate Upper Paleolithic occupation-probably representing modern humans-at archaeological sites on the Don River in Russia 45,000 to 42,000 years ago. The oldest levels at Kostenki underlie a volcanic ash horizon identified as the Campanian Ignimbrite Y5 tephra that is dated elsewhere to about 40,000 years ago. The occupation layers contain bone and ivory artifacts, including possible figurative art, and fossil shells imported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 9 publications
3
57
0
1
Order By: Relevance
“…Moreover, OSL ages of 47.7 ± 3.4 and 32.2 ± 2.3 ka, respectively, were obtained for samples bracketing the same ash layer in another profile at Kostenki-Borshchevo (Anikovich et al, 2007). More recent luminescence investigations on Romanian loess sections containing the CI ash layer also provide strong support for our luminescence results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, OSL ages of 47.7 ± 3.4 and 32.2 ± 2.3 ka, respectively, were obtained for samples bracketing the same ash layer in another profile at Kostenki-Borshchevo (Anikovich et al, 2007). More recent luminescence investigations on Romanian loess sections containing the CI ash layer also provide strong support for our luminescence results.…”
Section: Discussionsupporting
confidence: 83%
“…The CI tephra, originating in the Phlegrean fields of southern Italy and dated by 40 Ar/ 39 Ar to 39.28 ± 0.11 ka (De Vivo et al, 2001) has been widely identified in lacustrine, marine, loess and cave sediments, extending across the eastern Mediterranean and eastern Europe to north Africa and the Russian Plain (Thunnel et al, 1978;Ton-That et al, 2001;Pyle et al, 2006;Anikovich et al, 2007). The CI eruption occurred during a significant time period coinciding with the extremely cold climate phase Heinrich Event 4, the arrival of anatomically modern humans into Europe and the disappearance of the Neanderthals from the continent (Lowe et al, 2012;Fitzsimmons et al, 2013, Fedele et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In the Russian Plain, the Spitsynian from level II of Kostenki 17, so far an isolated occurrence but lacking in bifacial foliates and featuring a developed blade/bladelet, fully UP technology that sets it apart from the Streletskayan (Sinitsyn 2003), probably represents, given these traits and its stratigraphic position under a CI tephra deposit (Anikovich et al 2007), an intrusion into the regional archaeological record akin to the Protoaurignacian of regions to the west. In this case, a clear connection with cultural developments in the Near East is apparent in the fact that a perforated Columbella shell, modern representatives of which are today conined to the Mediterranean Basin, more than 700 km away, was recovered in level IVb of Kostenki 14; the associated stone-tool assemblage, although of uncertain cultural afiliation, is unambiguously UP and dates to the time range of the Protoaurignacian.…”
Section: The Transitional Phasementioning
confidence: 99%
“…Erst infolge des eintretenden Klimawandels wurden die Menschen sesshaft mit Vorratshaltung, Ackerbau und nachfolgender Viehzucht, wuchs die Bevölkerungszahl, kam es (einige tausend Jahre später) in den Zentren zu Städten und an den Peripherien zu Expansionen, also Völkerwan-derungen in meist schon besiedelte Gebiete hinein (Diamond & Bellwood 2003 (Mellars 2005). Vor 85.000 Jahren verließ eine Gruppe des modernen homo sapiens Afrika, 3 deren Nachkommen sich nach und nach auf alle Kontinente verbreiteten; so erreichten die ersten Menschen Australien und Neuguinea vor ungefähr 50.000 Jahren, und nur wenig später sind auch Menschen am mittleren Don nachgewiesen (Anikovich 2007 (Hauser et al 2002, Ott 2007. Später könnte er nicht liegen, weil dann nicht erklärbar wäre, warum Australier, Afrikaner, Asiaten und Amerikaner dieselbe Art von Sprachlernfähigkeit haben (falls sie denn genetisch verankert ist); für die Kinder überall auf der Welt gibt es keine Beschränkung darin, welche Sprache sie lernen können.…”
unclassified